Effects of Dl-3-n-butylphthalide on neurological function, hemodynamics and Hcy concentration in cerebral hemorrhage: a systematic review and meta-analysis - Ma, Yingqi; Guo, Chenchen; Wang, Yiguo; Liu, Xinxin (Frontiers in Pharmacology, 2024)
Background Dl-3-n-Butylphthalide (NBP) has emerged as a potential therapeutic agent for cerebral hemorrhage, despite not being included in current guideline recommendations. Investigating the underlying physiological and pathological mechanisms of Dl-3-n-Butylphthalide in cerebral hemorrhage treatment remains a critical area of research. Objective This review aims to evaluate the efficacy of Dl-3-n-Butylphthalide in cerebral hemorrhage treatment and elucidate its potential biological mechanisms, thereby providing evidence to support treatment optimization. Methods A comprehensive search of seven electronic databases (PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, VIP, and Wanfang Database) was conducted for studies published up to September 2023. Screening and data extraction were performed by a team of researchers. The Cochrane collaboration tool was utilized for risk bias assessment, and Revman 5.3 along with Stata 17.0 were employed for statistical analysis. Outcomes We searched 254 literature, and 19 were included in this meta-analysis. The results showed that Dl-3-n-Butylphthalide improved the clinical efficacy rate (RR = 1.25, 95% CI 1.19–1.31; p = 0.00), quality of life (MD = 13.93, 95% CI: 11.88–15.98; p = 0.000), increased cerebral blood flow and velocity, reduced cerebral edema volume, Hcy concentration, and did not have obvious adverse reactions (RR = 0.68, 95% CI: 0.39–1.18; p = 0.10). Conclusion This meta-analysis is the first to demonstrate the potential of Dl-3-n-Butylphthalide in treating cerebral hemorrhage. It suggests that Dl-3-n-Butylphthalide may alleviate clinical symptoms by modulating neurological function and improving hemodynamics. Our findings provide robust evidence for incorporating Dl-3-n-Butylphthalide into cerebral hemorrhage treatment strategies, potentially guiding future clinical practice and research. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/ display_record.php?RecordID=355114, Identifier CRD42022355114.